Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
x = - [tex]\frac{3}{2}[/tex], x = 3
Step-by-step explanation:
To find the zeros let p(x) = 0 , that is
2x² - 3x - 9 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 2 × - 9 = - 18 and sum = - 3
The factors are - 6 and + 3
Use these factors to split the x- term
2x² - 6x + 3x - 9 = 0 ( factor the first/second and third/fourth terms)
2x(x - 3) + 3(x - 3) = 0 ← factor out (x - 3) from each term
(x - 3)(2x + 3) = 0
Equate each factor to zero and solve for x
2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = - [tex]\frac{3}{2}[/tex]
x - 3 = 0 ⇒ x = 3
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.